Proceedings of the 26th International Symposium on Advancement of Construction Management and Real Estate - Guo, Hongling; Fang, Dongping; Lu, Weisheng; Peng, Yi. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book of CRIOCM 2021 (26th International Conference on Advancement of Construction Management and Real Estate) presents the latest developments in real estate and construction management around the globe. The conference was organized by the Chinese Research Institute of Construction Management (CRIOCM) working in close collaboration with Tsinghua University. Written by international academics and professionals, the book discusses the latest achievements, research findings and advances in frontier disciplines in the field of construction management and real estate. Covering a wide range of topics, including building information modeling, big data, geographic information systems, housing policies, management of infrastructure projects, intelligent construction and smart city, real estate finance and economics and urban planning and sustainability, the discussions provide valuable insights into the implementation of advanced construction project management and real estate market in China and abroad. The book offers an outstanding resource for academics and professionals.
BIM and emerging technologies -- Built environment -- Construction waste management -- CSR and industry governance -- Green building -- Housing price and policy -- Innovation of construction management theory and practice -- Land use and transportation -- New construction technology and application -- New-type urbanization -- Occupational safety and health -- Urban regeneration -- Urban resilience.
Keywords: Real estate management; Construction industry-Management.; Urban economics; Real estate business; Real Estate Management; Construction Management; Urban Economics; Real Estate Economics